Redução da resistência de geogrelhas devido a danos químicos causados por resíduos de construção e demolição reciclados - Silvestre, Gabriel Ribeiro (2019)
The growth of construction generates an increasing volume of construction and demolition waste (CDW) in the urban environment. Recent studies have shown the feasibility of using these materials in reinforced soil structures (RSS) with geosynthetics. In this context, most of these studies focused on investigations of the performance and mechanical damage suffered by geosynthetics during installation. However, chemical and environmental damage to geogrids from contact with the recycled construction and demolition waste (RCDW) over time is also important information for the design of these structures. Therefore, the main objective of this work was to evaluate the reduction of geogrid tensile strength due to chemical damage caused by RCDW when exposed to damage and different saturation scenarios. Characterization tests were performed on RCDW samples collected from a recycling plant. In-field test facilities were constructed to allow two types of geogrid (PET and PVA) being in contact with RCDW under three saturation conditions (dry, saturated and exposed to rain). Geogrid specimens were exhumed at two moments (1st and 2nd exhumations) to verify the occurrence and intensification of damage using SEM, EDX and tensile strength tests. During the exhumations, samples of RCDW and water were collected to geotechnical and chemical tests, respectively. Given the geotechnical focus of this study, tests commonly used for soil characterization were performed. Other tests were carried out to observe the chemical and composition characteristics of RCDW (pH and gravimetric composition). The results of the RCDW characterization showed characteristics very similar to those of granular soils, low variability of geotechnical parameters and alkaline characteristics. The SEM results showed the impregnation of RCDW on the geogrids. However, it was not possible to identify such aggregations by morphological analysis and EDX. Chemical analyzes in the liquids extracted from the in-field test facility during the exhumations processes indicated that RCDW could be classified as non-inert material. The tensile test results showed that PET geogrids presented a greater reduction of strength when exposed to the rainwater contact. Other parameters (strain and strength at 2% strain) were influenced differently. The results of PVA geogrids (2nd exhumation) showed that only the damaged samples in contact with rainwater showed no strength reduction. Regarding to other parameters evaluated of PVA geogrid, it was observed that the presence and type of water caused diverse changes. It is possible to conclude that the contact with water was the most significant factor in the geogrid strength changes when in contact with RCDW, with the effects being intensified on the damaged samples. However, the reduction factors observed could be implemented to designing RSS using RCDW and geosynthetics, thus demonstrating that RCDW could be employed as a friendly environmental backfill material.